Dasar Pertimbangan Hakim dalam Menjatuhkan Putusan Pidana Ujaran Kebencian Atas Nama Terdakwa Habib Bahar Bin Smith - Andika Pradipta Putra W; Chepi Ali Firman Zakaria (UNISBA Press, 2024)
Abstract. The development of information and communication technology has led to increasingly open opportunities for individuals to interact with others on social media. But not infrequently comments on social media often lead to giving blasphemy or hate speech to an individual or other group that can cause polemics between individuals or groups, one of which is BAHAR bin SMITH. BAHAR bin SMITH was submitted to the Bandung District Court by JPU, alleging that he had committed hate speech during his lecture in December 2021 in Margaasih District, Bandung Regency in commemoration of the Birthday of the Prophet Muhammad SAW. Some of the content of his lecture was provocative, containing hate speech against the government to the Indonesian Police institution, which actually Habib Rizieq was punished not for commemorating the Birthday of the Prophet Muhammad SAW, however, due to violations of the Health Process in Petamburan and the Bogor Hospital Swab case. As for the death of 6 FPI fighters, the actual facts from the Visum et Repertum Results, the death of 6 FPI fighters, due to 2 gunshot wounds, there were no injuries due to persecution due to having their nails removed, skinned, and their genitals burned. This study aims to know, study, and analyze whether the acts committed by the accused BAHAR bin SMITH meet the criteria for hate speech; The specifics of the research on this case are descriptive analytical, with the method of juridical-normative approach, the analysis is qualitative juridical. Legal considerations that handed down a verdict on hate speech against this act, BAHAR bin SMITH has been sentenced by the Bandung District Court to imprisonment for 6 months and 15 days, as referred to in the Bandung District Court decision Number 220/Pid.Sus/2022/PN.Bdg dated August 16, 2022 which was later corrected by the Bandung High Court to 7 months as referred to in the Court decision. Abstrak. Perkembangan teknologi informasi dan komunikasi memungkinkan individu berinteraksi di media sosial, namun seringkali muncul komentar yang bersifat hujatan atau ujaran kebencian, seperti dalam kasus BAHAR bin SMITH. BAHAR bin SMITH dihadapkan ke Pengadilan Negeri Bandung karena dianggap melakukan ujaran kebencian dalam ceramahnya pada peringatan Maulid Nabi Muhammad SAW di Margaasih, Kabupaten Bandung, Desember 2021.Penelitian ini bertujuan untuk menilai apakah tindakan BAHAR bin SMITH memenuhi kriteria ujaran kebencian dengan pendekatan yuridis-normatif dan analisis kualitatif. Ceramahnya dianggap provokatif karena berisi ujaran kebencian terhadap pemerintah dan kepolisian terkait kasus Habib Rizieq dan kematian 6 laskar FPI.Pengadilan Negeri Bandung menjatuhkan hukuman 6 bulan 15 hari, yang diperbaiki Pengadilan Tinggi Bandung menjadi 7 bulan. Penelitian menunjukkan bahwa pertimbangan hukum yang mendukung putusan tersebut adalah adanya elemen ujaran kebencian dalam ceramah BAHAR bin SMITH yang dapat menimbulkan kerusuhan sosial. Dengan demikian, hukuman tersebut dianggap sesuai dengan norma hukum yang berlaku di Indonesia.